Afetividade e ambiente esportivo: sentimentos e emoções de atletas de competição - Viana, Lívia Gomes (2009)
This research aimed to explore the emotions in the environment of sport links between Environmental Psychology and Psychology of Sports. This study enabled the formulation of a new relationship between emotion and sporting environment from studies of affection. For this, we investigated the affective (feelings and emotions) from competition of athletes from various sports. We utilize the methodology of the seizure of affection affective maps, the methodology of scientific research was coined by Bomfim (2003) in their search for doctorate. From the maps the emotional feelings of the subjects investigated in relation to environments using drawings and metaphors, allowing the production of images that point to understand the affection for environments. 81 athletes participated in this research, chosen for convenience and saturation, formalizing an analytical study of type-interpretative (qualitative) with an additional statistical analysis provided by a Likert scale. The maps allow the construction of affective emotional images that relate to linking the individual to the environment when there are images that generate positive esteem and lead to action of individuals. But may also generate negative estimates in respect of the subject with the environment. In this study, athletes in competition produced images of belonging, pleasantness, attraction, contrast, insecurity and destruction. The images were positive with estimates of the pleasantness, proximity, contrast and attraction, while the negative images that were generated estimates of the destruction and insecurity. The image of pleasantness was prepared by the majority of the athletes it relates to the environment with good qualities and feelings as a great environment, beautiful and harmonious. The image of belonging, individuals who perceive the relationship with the environment as a good opportunity for good approximation to their meetings and similar. The image contrast is related to the sporting environment in which the athletes to represent feelings, emotions and words that have a contradictory positive and negative polarization. The image of attraction is that in which the athletes perceive their environment as offering good growth, learning and overcoming. Those negative images with esteem, insecurity and destruction, were prepared by a minimum of respondents, but has a rich reflection on the possibility of the sports environment is not enhanced the actions of athletes. These results were linked to the meaning of sports performance prepared by the athletes. We note that sports environments that generated images with positive esteem - pleasantness, proximity, contrast and attraction - seems to promote an idea of performance targets linked to the process contributing to the action of the athletes. For the images with negative estimates found that the concept of performance targets linked to the outcome of hampering the action of the athletes and their linkage with the sports environment. From these results the understanding of emotions in the sports environment from affection, could enable technicians, athletes and sports psychologists plan the involvement of athletes in sports not only focusing on the physical preparation, but also paying attention to the identification of athletes with their environments, because this binding was shown to be enhanced the actions of individuals which can lead to an improvement in performance.